Tigecycline pharmacokinetics, tolerability, safety, and effect on intestinal microflora in healthy Japanese male subjects - Yamashita, Noriaki; Matschke, Kyle; Gandhi, Ashesh; Korth-Bradley, Joan (Journal of clinical pharmacology, 2014)
Safety, tolerability, and pharmacokinetics of tigecycline in 76 healthy Japanese subjects were determined in three randomized, double-blind, placebo-controlled studies. Subjects in an ascending single-dose study (n = 40) received 25-150 mg intravenously, whereas subjects in two multiple-dose studies received every 12-hour (q12h) dosing with 25 mg (n = 10) or 25, 50, or 100 then 50 mg (n = 30). Serial blood samples and urine were collected, drug concentrations determined, and pharmacokinetic parameters calculated. Fecal samples were also collected in the second multiple-dose study. After 10 days of tigecycline 50 mg q12h, mean ± standard deviation pharmacokinetics in 8/10 subjects were: maximum concentration 1,118 ± 127 ng/mL, area under the concentration-time curve 0-12 hours 3,261 ± 937 ng h/mL, clearance 0.25 ± 0.05 L/h/kg, half-life 60.7 ± 23.4 hours, and volume of distribution 11.9 ± 2.3 L/kg. The most common adverse events were nausea and vomiting. Changes in total bilirubin were also observed. Enterococci in the intestinal microflora were reduced, whereas the number of Enterobacteriaceae and Bacteroides remained relatively constant. Several strains of Bacteroides spp. resistant to tigecycline treatment were found in fecal samples on days 30 and 31. The pharmacokinetic profile of tigecycline was similar to non-Japanese subjects; tolerability and change in intestinal microflora were also similar.